ANALISIS PENDAPATAN USAHATANI TOMAT (LYCOPERSICUM ESCULENTUM MILL.). (DI DUSUN BRUMBUN DESA LAMONGREJO KECAMATAN NGIMBANG KABUPATEN LAMONGAN) - Hamidah, Emmy (Universitas Islam Darul Ulum, 2017)
Tomatoes are very good for preventing and treating various diseases, such as canker sores because they contain vitamin c. fresh fruit in addition to the direct consumption of tomatoes, can also be used as a flavoring a wide variety of dishes such as soups, gado-gado, sambal, and can also be used as industrial materials to be consumed in processed form, for example, to drink tomato juice, tomato juice, ice and concentrates. A wide range of uses that can give you an advantage, both for consumers, manufacturers, as well as society in General. In this study a tomato farming on land 1 Ha of which require the total cost up to Rp. 82,220,000 is getting yields as much as 16,080 kg with acceptance of Rp. 160,800,000. Then in may a profit amounting to Rp. 78,580,000 with R/C Ratio 1.9 indicating that a tomato farmer in the hamlet of Brumbun Subdistrict Ngimbang Lamongan is profitable and viable to continue.